Evaluation of Bio-Drying Cow Dung with Inoculation of Bacillus sp. as Refuse Derived Fuel (RDF) Material - Febriantoko, Ardiansah; Jayanegara, Anuraga; Sholeha, Novia Amalia; A'yuni, Qurrota (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Global warming, driven in part by livestock manure emissions, poses a major environmental challenge. Refuse Derived Fuel (RDF) offers a waste-to-energy solution by converting solid cow manure into an energy source. This study investigated the impact of Bacillus sp. inoculation on the biodrying process of cow dung. The main challenge in processing cow manure into RDF is ensuring that the moisture content and calorific value meet the minimum RDF standards. Therefore, a biodrying process was carried out on cow manure to achieve these required standards. Biodrying performance was assessed based on drying time, moisture content, pH, and calorific value. The results show that inoculation with Bacillus sp.. The results showed that inoculation with Bacillus sp. at 10⁶ log cfu ml⁻¹ kg⁻¹ yielded the most efficient outcome, achieving the fastest drying time (12 days), lowest moisture content (9.64%), optimal pH (7.8), and highest calorific value (2,656.5 kcal/kg). These findings confirm a direct link between moisture reduction and calorific improvement. Hence, bio-dried cow dung treated with inoculation of Bacillus sp. 106 log cfu ml-1 Kg-1 is recommended as a viable RDF material.